Village Financial Performance Analysis Using Effectiveness, Efficiency, Independence, And Growth Ratios In Dajan Peken Village, Tabanan Regency, 2022-2024 - Annisa Ramadhani Siregar; Anggi Pratama Nasution; Puja Rizqy Ramadhan (Utan Kayu Publishing, 2025)
This study aims to analyze the financial performance of Dajan Peken Village, Tabanan Regency, during the 2022–2024 period using effectiveness, efficiency, independence, and growth ratios. This study uses a quantitative approach with secondary data obtained from the Village Budget (APBDes) realization report. The results show that the effectiveness ratio is in the effective to very effective category, meaning the village is able to consistently realize its revenue targets. However, the efficiency ratio indicates that expenditure management is not optimal because village expenditure tends to approach or exceed revenue in some years. The independence ratio shows a very low level, so the village is still dependent on government transfer funds. Meanwhile, the revenue growth ratio shows a positive trend from year to year, reflecting an increase in the village's fiscal capacity. Overall, the village's financial performance is quite good in terms of effectiveness and growth, but still needs to be improved in terms of efficiency and fiscal independence